INTEGRASI NILAI-NILAI BUDAYA ISLAM DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Priarni, Rina (INSPIRASI (Jurnal Kajian dan Penelitian Pendidikan Islam), 2019)
It has a very important role in human life. Religion a guide in the pursuit of a life meaningful, peaceful and dignified.Know how important the role of religion for the people, so internalization religious values in the life of every personal, turn out to be inevitable traveled through education good education in, family environment , school and the community.The purpose of this research is to find how intregasi values islamic culture in learning islamic education. The research is qualitative research data made in research library ( library research ) antropologis. pedagogik by approach. We found it is islamic local culture is a customs in a community that is understood as one an integral part in the community whether it is legally, moral and ethical interactions among. The local culture of god confidence a community as something to be maintained is typical for a community. students know, cultural activities especially, local culture without knowing the meaning of such activities. Islamic and cultural values that islamic education be integrated with inculcated by teacher told students following claims that religion are taught with human vision to create islamic culture devotion to god and pleaseth, noble and was intended to produce human, honest, fair of doing, ethical, respect each other, discipline harmonious and productive, both personal and socially.